Detection of avian metapneumovirus subtypes in turkeys using RT-PCR - Ongor, H.; Karahan, M.; Kalin, R.; Bulut, H.; Cetinkaya, B. (British Veterinary Assoc, 2010)
This study investigated the prevalence of avian metapneumovirus (aMPV) and the detection of molecular subtypes of field strains of the virus using RT-PCR in clinically healthy turkeys and those showing signs of respiratory disease. In the RT-PCR examination of 624 tracheal tissue samples collected from a local turkey abattoir, 2.9 per cent (18/624) of samples tested positive. In the examination of tracheal swab samples collected from flocks with respiratory problems, 18 of 20 samples tested positive. When the results were assessed at flock level, aMPV infection was detected in only one of the 23 clinically healthy turkey flocks, whereas all four flocks with respiratory problems were infected. Molecular typing using primers specific to the attachment glycoprotein (G) gene showed that all 36 positive samples belonged to subtype B. Partial sequence analysis of DNA samples showed 95 per cent homology between the field types and the reference strain aMPV subtype B. Whereas clinically healthy turkeys had been vaccinated with a subtype A virus vaccine, the flocks with respiratory problems had been vaccinated with a subtype B virus vaccine. Despite four blind passages of RT-PCR-positive samples on Vero and chicken embryo fibroblast cells, no cytopathic effect was detected by microscopic examination.
Keywords: Rhinotracheitis Virus; Pneumovirus; Chickens; Infection; Strains; Field; Vaccine